Effectiveness of the use of the school budget activity plan application in managing school operational assistance funds at Elementary School Number 1 Abiansemal in 2024 - Rahayu, Ni Made Pitri; Wirata, Gede; Astawa, I Wayan (Priviet Social Sciences Journal, 2024)
The management system for school operational assistance funds has evolved to in- corporate information and communication technology through the School Budget Activity Plan Application, commonly referred to as ARKAS. The Ministry of Ed- ucation, Culture, Research, and Technology developed the ARKAS innovation to facilitate the management of school operational assistance funds received by each educational institution. This study aims to understand why the effectiveness of using the School Budget Activity Plan application at Elementary School Number 1 Abi- ansemal has not yet been optimized. A qualitative method was employed to explore information about the phenomenon, supported by a descriptive approach, which en- abled the creation of relationships with informants, allowing the researcher to obtain new data. The data sources were obtained from interviews and documents related to the research. Data collection was conducted through documentation, interviews, and observation at the research location. Subsequently, the data were analyzed using data reduction, data presentation, and conclusion drawing. The results of this study indicate that the suboptimal effectiveness in using the School Budget Activity Plan application for managing school operational assistance funds at Elementary School Number 1 Abiansemal is due to insufficient dissemination by relevant authorities regarding the understanding of ARKAS and inadequate supporting infrastructure. However, improvements in several components are necessary to enhance the effective- ness of managing school operational assistance funds through ARKAS. This includes the need for training and socialization to improve understanding of ARKAS usage in terms of planning, reporting, and realization, as well as creating synergy between school operators and district operators to ensure that the information conveyed is easily understood.